Anybody out there? Der Begriff der Masse im Crowdsourcing - Andrea Schilz (Zeitschrift für digitale Geisteswissenschaften)
The article critically discusses the concept of ›the mass‹ from the perspective of crowdsourcing application fields. It provides, also considering historic aspects, an overview of specific methods used in the field of citizen science and in digital humanities projects.